2020
DOI: 10.1101/2020.01.25.919340
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Liquid-liquid phase separation of full-length prion protein initiates conformational conversionin vitro

Abstract: What initiates the sporadic misfolding process of PrP C remains to be elucidated. Here, we show that rPrP undergoes LPS at the interface of ATPS of polyethylene glycol (PEG)/dextran; also, subsequent liquid-solid phase transition attributed to the maturation of β-sheet structure initiated the spontaneous conversion of rPrP into PrP Sc -like amyloid. The intrinsically disordered region of PrP, residues 23-89, and kosmotropic anions were essential for the overall reaction. As the conversion of the protein procee… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…1 A ). Both before and after TEV cleavage, GFP fluorescence was evenly distributed, indicating that neither C1 nor C2 formed biomolecular condensates under these conditions, corroborating recent results ( 41 ). Of note, the lack of LLPS was not due to inefficient TEV cleavage ( Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…1 A ). Both before and after TEV cleavage, GFP fluorescence was evenly distributed, indicating that neither C1 nor C2 formed biomolecular condensates under these conditions, corroborating recent results ( 41 ). Of note, the lack of LLPS was not due to inefficient TEV cleavage ( Fig.…”
Section: Resultssupporting
confidence: 90%
“…The ability of full-length PrP to form biomolecular condensates has been described recently ( 41 , 42 , 43 , 44 , 45 ); however, the underlying molecular mechanisms that drive the formation of liquid-like droplets remain unknown. In the present study, we analyzed phase separation of full-length PrP and its major proteolytic fragments N1, N2, C1, and C2.…”
mentioning
confidence: 99%
“…Proteins that can undergo LLPS, such as FUS, TDP-43, and Tau protein, usually contain repetitive domains or intrinsically disordered regions (IDR) (54)(55)(56)(57). Numerous studies identified that a variety of amyloid aggregation-prone proteins initiate aggregations through LLPS (58)(59)(60)(61). α-Syn has three IDRs and multiple low-complexity domains.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of equating in vitro/in silico results with in vivo results, these structural biology effects and their allelic hierarchy tally with endpoints scored in PrP-expressing RK13 cells, specifically the heightened formation of PrP immunoreactive puncta and detergent insoluble complexes in S3 cells grown in Cbl-containing cell medium. A recent and perhaps parallel avenue of work on PrP concerns liquid-liquid phase-separation (LLPS) effects, often studied with recombinant protein presented on glass surfaces (99)(100)(101). Notably, the PrP N-terminal regionthe site of the S3 allele amino acid substitutionshas been deduced as being important for phase separation effects (100,101), a result in accordance with possession of two polybasic regions (101), low sequence complexity and regular positioning of aromatic residues as per the "sticker and spacer" model of phase transitions (102,103).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…A recent and perhaps parallel avenue of work on PrP concerns liquid-liquid phase-separation (LLPS) effects, often studied with recombinant protein presented on glass surfaces (99)(100)(101). Notably, the PrP N-terminal regionthe site of the S3 allele amino acid substitutionshas been deduced as being important for phase separation effects (100,101), a result in accordance with possession of two polybasic regions (101), low sequence complexity and regular positioning of aromatic residues as per the "sticker and spacer" model of phase transitions (102,103). It is also striking that the PrP paralog protein shadoo has an N-terminal low complexity region, in this case an RGG repeat domain (104,105), with this class of proteins being well-accepted as undergoing LLPS (106).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%